Peranan Hukum Dalam Mewujudkan Kesejahteraan Masyarakat Indonesia - Arini Nova Istiqomah; Yasmine Amira Uzhma; Syifa Fadilah (Universitas Sains dan Teknologi Komputer, 2024)
The Republic of Indonesia is a legal state where power is subject to law. The consequence of the rule of law is that law has the highest position in government.